ILMU DAN EKSISTENSI KEBAHAGIAAN MENURUT AL-GHAZALI - , Habibi (Dirosat : Journal of Islamic Studies, 2016)
This article discusses about al-Ghazali’s concept, one of the Islamic greatest ulama, philosopher and Sufism. It would like to describe about the knowledge and happiness existence. For Al-Ghazali, the happiness couldn’t be released from the knowledge because by studying and inspiring of knowledge, the human being will be in happiness. And also, the achieved happiness is always running parallel with the level of the applied knowledge. The method in this journal is using library research and content analyzing. Al-Ghazali explained that body existence (material) would result the transitory happiness, while the soul existence (immaterial) would result the eternal happiness from the world up to the beyond. Al-Ghazali said that knowledge epistemology is divided by two sources of seeking. The first is humanity source, and the second is divinity source.